DILEMA ISLAMIC STUDIES, DILEMA PENDIDIKAN ISLAM - Abdul Munir Mulkhan (Islamic University of Indonesia, 2002)
The developing of the Integrated Islamic School in recent years appears the problem especially the using of the term